Biodiversity of Angola 2019
DOI: 10.1007/978-3-030-03083-4_15
|View full text |Cite
|
Sign up to set email alerts
|

The Mammals of Angola

Abstract: Scientific investigations on the mammals of Angola started over 150 years ago, but information remains scarce and scattered, with only one recent published account. Here we provide a synthesis of the mammals of Angola based on a thorough survey of primary and grey literature, as well as recent unpublished records. We present a short history of mammal research, and provide brief information on each species known to occur in the country. Particular attention is given to endemic and near endemic species. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 113 publications
(116 reference statements)
0
18
0
Order By: Relevance
“…The use of modern cluster analysis techniques was taken further, at an Angolan level, by Rodrigues et al (2015). Based on a cluster analysis of data for 9880 records of 140 species of ungulates, rodents and carnivores at a quarter degree resolution, the study found general congruence with that of Linder et al (2012) and the earlier divisions of Angola's biogeography (Beja et al 2019). Rodrigues et al (2015) identify 18 indicator species for their four main divisions, which agree with the groupings based on field surveys undertaken in the 1970s (Huntley 1973) that also included the enclave of Cabinda, which was not included in the Rodrigues et al (2015) analyses.…”
Section: Statistical Regionalisationmentioning
confidence: 84%
See 1 more Smart Citation
“…The use of modern cluster analysis techniques was taken further, at an Angolan level, by Rodrigues et al (2015). Based on a cluster analysis of data for 9880 records of 140 species of ungulates, rodents and carnivores at a quarter degree resolution, the study found general congruence with that of Linder et al (2012) and the earlier divisions of Angola's biogeography (Beja et al 2019). Rodrigues et al (2015) identify 18 indicator species for their four main divisions, which agree with the groupings based on field surveys undertaken in the 1970s (Huntley 1973) that also included the enclave of Cabinda, which was not included in the Rodrigues et al (2015) analyses.…”
Section: Statistical Regionalisationmentioning
confidence: 84%
“…What is equally important in biogeographic analysis is the detection of patterns of endemism and diversity at dispersed scales -such as the Angolan Escarpment Zone -described by Hall (1960a) and subsequently recognised by many workers as of great biodiversity and evolutionary importance (Huntley 1973(Huntley , 1974a(Huntley , 2017Hawkins 1993;Mills 2010;Clark et al 2011). Indeed, each taxon-based account in this volume, on plants (Goyder and Gonçalves 2019), odonata (Kipping et al 2019), lepidoptera (Mendes et al 2019), fishes (Skelton 2019), birds (Dean et al 2019), amphibians (Baptista et al 2019), reptiles (Branch et al 2019) and mammals (Beja et al 2019) draws attention to the importance of the Angolan Escarpment as a centre of endemism and speciation. Hall (1960a) explained her recognition of the importance of the Angolan Escarpment as the major speciation hotspot for birds in Angola by it: (i) creating a barrier between arid-adapted species of the coastal plains and of the miombo woodlands of the plateau, (ii) creating a steep ecological gradient, and (iii) functioning as a refuge for moist forest specialists that were isolated here during the dry periods of the glacial cycles.…”
Section: The Biological Importance Of the Angolan Escarpmentmentioning
confidence: 91%
“…The populations of Giant Sable Antelope and Red Lechwe in Luando, each estimated at 2000 in 1972 (Huntley 1972), had dropped to less than 100 Giant Sable and with Lechwe on the verge of extinction by 2017 (Vaz Pinto 2018. Savanna Elephant, Blue Wildebeest and Eland, abundant in Bicuar in the 1970s, had fallen to low numbers by 2017 (Beja et al 2019). Across Angola, wildlife populations declined precipitously after 1974, but remarkably, very small but tenacious surviving populations of most species, including top predators such as Lion, Leopard, Cheetah and Wild Dog, have held out (Beja et al 2019).…”
Section: Wildlife Populationsmentioning
confidence: 99%
“…Savanna Elephant, Blue Wildebeest and Eland, abundant in Bicuar in the 1970s, had fallen to low numbers by 2017 (Beja et al 2019). Across Angola, wildlife populations declined precipitously after 1974, but remarkably, very small but tenacious surviving populations of most species, including top predators such as Lion, Leopard, Cheetah and Wild Dog, have held out (Beja et al 2019). Of considerable conservation concern is the number of large mammal species for which no recently confirmed records are available, including Gorilla, Black Rhinoceros, Puku, Red Hartebeest and Lichtenstein's Hartebeest (Beja et al 2019).…”
Section: Wildlife Populationsmentioning
confidence: 99%
See 1 more Smart Citation